Evaluación del cocimiento de diferentes biovariedades de Caesalpinia spinosa (tara) frente a cepas de Staphylococcus aureus sensibles y resistentes a oxacilina - Guevara G., José María (2014)
Objectives: To determine three tara’s biovarieties antimicrobial activity against oxacillin sensitive and resistant Staphylococcus aureus strains. Design: Descriptive, prospective, analytical study. Setting: Instituto de Medicina Tropical Daniel A. Carrion, Facultad de Medicina, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Three tara biovarieties and Staphylococcus aureus strains. Interventions: Thirty-one S. aureus oxacillin-sensitive strains and 29 oxacillin-resistant strains isolated from clinical samples were studied against three tara varieties obtained in Huamanga, Huarochiri and Tarma. Tara’s poaching was prepared and blank discs were soaked in to use as antibiogram by disc difussion. Main outcome measures: Inhibition halos diameter. Results: All three poachings showed antimicrobial activity against Staphylococcus aureus strains; Huamanga’s poaching displayed larger inhibition halo against sensitive and resistant strains. Huarichiri’s poaching showed significant larger inhibition halo in oxacillin-resistant strains than in sensitive ones. Huarochiri’s poaching had less significant activity as compared with Huamanga and Tarma poachings. Conclusions: Huarochiri’s poaching exhibited less activity compared with those from Huamanga and Tarma.